2006
DOI: 10.1111/j.1753-4887.2006.tb00205.x
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role for Vitamin D on HIV Infection?

Abstract: Despite advances in the knowledge of vitamin D's potent immunomodulatory activity, its role on HIV disease progression is unknown. Decreased concentrations of 1␣,or 1,25(OH) 2 D, the active form of vitamin D, have been reported among HIV-infected people and attributed to defects in renal hydroxylation and increased utilization. A few studies also described low levels of 25-hydroxyvitamin D 3 , 25(OH)D, the vitamin obtained from solar synthesis and diet. An inverse association between 1,25(OH) 2 D concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
74
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 71 publications
2
74
2
2
Order By: Relevance
“…Before the advent of antibiotics, vitamin D was used in the treatment of bacterial infections (11)(12)(13)(14)(15). Many in vitro experiments confirm the action of its active form, 1,25(OH) 2 D, as a potent modulator of the immune system as well as its important role in calcium homeostasis.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Before the advent of antibiotics, vitamin D was used in the treatment of bacterial infections (11)(12)(13)(14)(15). Many in vitro experiments confirm the action of its active form, 1,25(OH) 2 D, as a potent modulator of the immune system as well as its important role in calcium homeostasis.…”
mentioning
confidence: 99%
“…Currently, more than 2/3 of the most recently infected individuals live in extremely poor regions of the world, where there is a high prevalence of nutritional deficiency. A lack of macronutrients has been associated with an increasing number of clinical manifestations and a rise in Aids-related mortality (1,11). Furthermore, studies have also revealed how the beneficial effects of being well-nourished with the necessary vitamin supplements can lead to an improvement in the immune systems of HIV-positive patients (11,12).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Most notably, the clinical course of tuberculosis (MTB) [13], as well as viral influenza and HIV infection, have been associated with vitamin D 3 status [14,15]. However, the capability of vitamin D 3 to modulate the host immune response to fungal infections is still unknown.…”
mentioning
confidence: 99%